Appraisal System in GoGo Dino Indonesian Lyric - Dhion Meitreya Vidhiasi (Jurnal Lingua Idea, 2021)
Movies or stories with superheroes theme always give color to the hearts of the audience. GoGo Dino film, which is an animated cartoon series from South Korea, also provides an excellent color to the audience. This study aims to analyze the Appraisal System used in the opening song lyrics of the Indonesian version of the GoGo Dino cartoon series. The research data obtained were then analyzed using Martin and White’s Appraisal System theory. Researchers used qualitative descriptive methods in explaining the results of the study. It can be seen that in the lyrics of the song, the author of the lyrics implements less use of affect and uses more judgment. The Judgment implementation shows that a person, or in this case, a superhero, is valued by his behavior parameters. From the behavior parameters, it can bring up the effect of affect which is a person’s reaction to the behavior.